2002
DOI: 10.1161/01.str.0000018405.59799.d5
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Disease and Evolution of Depressive Symptoms in the Cardiovascular Health Study

Abstract: Background and Purpose-Previous studies have reported an association between cerebrovascular disease and depressive symptoms. The Cardiovascular Health Study (CHS) provides an opportunity to examine the relationship between vascular brain pathology seen on neuroimaging and changes in depressive symptoms. Methods-The sample included 3236 CHS participants who had an MRI brain scan. Demographic variables, medical history, functional status, and apolipoprotein E genotype were obtained at baseline. Annual scores on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
114
2
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(126 citation statements)
references
References 40 publications
(43 reference statements)
5
114
2
5
Order By: Relevance
“…Cross-sectional associations between WMLs and depression have been shown repeatedly, especially for MRI and mainly from clinical studies (Greenwald et al, 1998;Ikram et al, 2010;Kumar et al, 2000;Kumar et al, 2002), although not all studies support this association (Rainer et al, 2006;Skoog et al, 1994). Our finding that WMLs preceded major depression is in agreement with three previous longitudinal studies using MRI (Godin et al, 2008;Steffens et al, 2002;Teodorczuk et al, 2007). However, two longitudinal population-based studies did not support this association (Ikram et al, 2010;Versluis et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Cross-sectional associations between WMLs and depression have been shown repeatedly, especially for MRI and mainly from clinical studies (Greenwald et al, 1998;Ikram et al, 2010;Kumar et al, 2000;Kumar et al, 2002), although not all studies support this association (Rainer et al, 2006;Skoog et al, 1994). Our finding that WMLs preceded major depression is in agreement with three previous longitudinal studies using MRI (Godin et al, 2008;Steffens et al, 2002;Teodorczuk et al, 2007). However, two longitudinal population-based studies did not support this association (Ikram et al, 2010;Versluis et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…The results from longitudinal population-based studies are conflicting. Three studies using MRI reported that WMLs increased the risk of subsequent depression (Godin et al, 2008;Steffens et al, 2002;Teodorczuk et al, 2007) while two could not confirm these findings (Ikram et al, 2010;Versluis et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
“…49,50 Depression frequently occurs in the early stages of AD and may result from both cell loss in key areas of the brain controlling emotions as well as a psychological reaction to cognitive loss. 4 Vascular changes such as white matter hyperintensities are a risk factor for both depression 51,52 and dementia, 53 and are associated with a high prevalence of depression in cross-sectional studies 54 . In our sensitivity analysis that excluded patients with an ICD-9 diagnosis of dementia in the 2 years after baseline, depression remained associated with an increased risk of dementia, suggesting that depression was less likely to be a prodromal symptom or secondary to dementia.…”
Section: Discussionmentioning
confidence: 99%
“…A white matter hyperintensity (WMH) score was determined by grading the extent of increased white matter signal intensity on the fluid-attenuated inversion recovery sequence images in the periventricular and subcortical white matter area. The grading was based on a 10-point scale (0 to 9), with a higher score indicating more severe white matter grade [32,36]. An example of WMH grading in control subjects and patients with MSA is illustrated in Fig.…”
Section: Methodsmentioning
confidence: 99%